PENGARUH WORD OF MOUTH, CITA RASA, DAN LOKASI TERHADAP LOYALITAS PELANGGAN PADA PENJUALAN MIE SEM BELIBIS DI ASEMBAGUS DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Kholida, Firda Ulfatul; Karnadi, Karnadi; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Marketing is a common activity undertaken by many individuals. Over the years, it has evolved significantly, as exemplified by the culinary business Mie Sem Belibis, which offers customizable levels of spiciness to suit consumer preferences. This study aims to analyze and examine the impact of word of mouth, taste, and location on customer loyalty in the sales of Mie Sem Belibis in Asembagus, with customer satisfaction as an intervening variable. This research employs a quantitative approach. The study's population comprises customers of Mie Sem Belibis, with a sample selected through random sampling. Data analysis and hypothesis testing are conducted using the Structural Equation Modeling - Partial Least Square (PLS-SEM) method. The results of the hypothesis testing for direct effects, conducted using the Smart PLS 3.0 application, reveal that word of mouth significantly influences customer satisfaction, taste significantly influences customer satisfaction, and location significantly influences customer satisfaction. However, word of mouth does not significantly influence customer loyalty, and taste does not significantly influence customer loyalty, whereas location significantly influences customer loyalty. Additionally, customer satisfaction significantly influences customer loyalty. The results of the hypothesis testing for indirect effects indicate that word of mouth significantly and positively influences customer loyalty through customer satisfaction, taste significantly and positively influences customer loyalty through customer satisfaction, and location significantly and positively influences Customer Loyalty through Customer Satisfaction.